If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2-11x=8
We move all terms to the left:
x2-11x-(8)=0
We add all the numbers together, and all the variables
x^2-11x-8=0
a = 1; b = -11; c = -8;
Δ = b2-4ac
Δ = -112-4·1·(-8)
Δ = 153
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{153}=\sqrt{9*17}=\sqrt{9}*\sqrt{17}=3\sqrt{17}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-11)-3\sqrt{17}}{2*1}=\frac{11-3\sqrt{17}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-11)+3\sqrt{17}}{2*1}=\frac{11+3\sqrt{17}}{2} $
| -10x-2/3=-52/3 | | X^2-15x-60=0 | | 2(4x-1)-5(7x)=25 | | (4-5x)-10=3 | | 2a+9+5a+14=180 | | 4x+47=x-5 | | 4(x+3)=3x+2+3x | | 12/5+8/5a=a+17/5 | | 2g+5-3g=6+7g | | x/2+15=23 | | -3x+11-3x=-2(4x-1)+15 | | 4x-4(5x+13)=28 | | 2+3x/4=18 | | 2p+15=×2 | | 14-3b=-10 | | 35-2x=90 | | 2(x+5)+3=5x-3(-4+x) | | 2(x-3)+4(x-5)=-2 | | 8x-4=6x-1 | | 6(1-2m=-7m+11 | | 29x^2-122x+90=25765 | | -3/2+1/3u=-6/7 | | 16−8x=14−7x | | 8x+7=136 | | 20j+3j-18j-3j=8 | | x/5+20=24 | | 3(x+3)=2(x+10) | | 24=6x+4x | | -y/5=51 | | 0=5r | | 16x+3=8+7x+4x | | 2x+1*2x-1=15 |